Marrow fat‐cortical bone relationship in β‐thalassemia: a study using MRI - Ismail, Umi Nabilah; Azlan, Che Ahmad; Khairullah, Shasha; Azman, Raja Rizal; Omar, Nur Farhayu; Md Shah, Mohammad Nazri; Jackson, Nicholas; Ng, Kwan Hoong (John Wiley and Sons, 2024)
Background: Growing evidence suggests that marrow adipocytes play an active role in the regulation of bone metabolism and hematopoiesis. However, research on the relationship between bone and fat in the context of hematological diseases, particularly β-thalassemia, remains limited. Purpose: To investigate the relationship between marrow fat and cortical bone thickness in β-thalassemia and to identify key determinants influencing these variables. Study Type: Prospective. Subjects: Thirty-five subjects in four subject groups of increasing disease severity: 6 healthy control (25.0 ± 5.3 years, 2 male), 4 β-thalassemia minor, 13 intermedia, and 12 major (29.1 ± 6.4 years, 15 male). Field Strength/Sequence: 3.0 T, 3D fast low angle shot sequence and T1-weighted turbo spin echo. Assessment: Analyses on proton density fat fraction (PDFF) and R2* values in femur subregions (femoral head, greater trochanter, intertrochanteric, diaphysis, distal) and cortical thickness (CBI) of the subjects' left femur. Clinical data such as age, sex, body mass index (BMI), and disease severity were also included. Statistical Tests: One-way analysis of variance (ANOVA), mixed ANOVA, Pearson correlation and multiple regression. P-values <0.05 were considered significant. Results: Bone marrow PDFF significantly varied between the femur subregions, F(2.89,89.63) = 44.185 and disease severity, F(1,3) = 12.357. A significant interaction between subject groups and femur subregions on bone marrow PDFF was observed, F(8.67,89.63) = 3.723. Notably, a moderate positive correlation was observed between PDFF and CBI (r = 0.33–0.45). Multiple regression models for both PDFF (R2 = 0.476, F(13,151) = 10.547) and CBI (R2 = 0.477, F(13,151) = 10.580) were significant. Significant predictors for PDFF were disease severity (βTMi = 0.36, βTMa = 0.17), CBI (β = 0.24), R2* (β = −0.32), and height (β = −0.29) while for CBI, the significant determinants were sex (β = −0.27), BMI (β = 0.55), disease severity (βTMi = 2.15), and PDFF (β = 0.25). Data Conclusion: This study revealed a positive correlation between bone marrow fat fraction and cortical bone thickness in β-thalassemia with varying disease severity, potentially indicating a complex interplay between bone health and marrow composition. Evidence Level: 2. Technical Efficacy: Stage 3. © 2024 International Society for Magnetic Resonance in Medicine.